Overtraining in swimming - Read, P.
In conclusion overtraining is caused by the athlete continually failing to recover from hard training, this could be due to high workloads and not enough recovery or it could be the result of poor eating habits. Coaches of swimming need to look out for the early signs of overtraining in their athletes and need to promote recovery techniques between and maybe even during training sessions. If an athlete becomes overtrained distance and intensity need to be lowered immediately so the athlete can recover and get back to the performance levels they were previously at. If this does not occur the athlete will become sick or injured and will not be able to train. Overtraining can be managed and prevented, in doing this athletes will be better off in the long term.